Axially loaded of cold-formed steel section with opening - Ruzaim, Ruslan (2018)
Cold-formed steel structural elements have been widely used in the construction industry and have emerged as a preferred economical solution for single-storey commercial and industrial buildings. Cold formed steel built-up sections are commonly used as compression elements to carry larger loads when a single section is insufficient. However, the built-up sections exhibit some unique buckling behaviors which the current codes do not have comprehensive provisions. This is ambiguous as the behavior of hot rolled steel is different from cold formed steel. This research will be concentrating on open built-up section or I-section. Structural members of cold-formed steel usually come with the presence of perforations. Perforations is a hole or opening that are made on the cold-formed steel to ease construction work. It usually provided with different shapes and size based on its function such as to accommodate electrical, plumbing and air conditioner or heating services In addition, very few studies have been carried out to study cold formed steel built-up sections such as back-to-back C-channel column without a gap, back-to-back C-channel column with a gap, battened, and laced columns. Thus, the aim of this research is to determine the ultimate load of cold-formed steel with and without opening through experimental studies. A total of 8 samples were tested in this experiment. Each sample has a nominal thickness of 1.2 mm and the same length of 600 mm columns, but different types of sections that are single sections and built-in sections, and diameters of web lengths of 103 mm and 203 mm. compressed between the supported end only at both ends. The result of this experiment shows that the ultimate load of each sample varies greatly on the perforation position and the web length. The result is presented in three section which are load vs. vertical displacement, load vs. horizontal displacement and buckling behavior.